Privacy: a Real-World Problem with Fuzzy Boundaries - Lincoln, T. L. (Methods of Information in Medicine, 1993)
Response to: Kluge E-H W. Advanced patient records: some ethical and legal considerations touching medical information space. Meth Inform Med 1993; 32: 95-103